Acreditação no varejo da indústria têxtil-confecção (ModaPalavra e-periódico, 2014)
The accreditation guarantees the existence of quality management systems in the organization, and be situated more strongly in healthcare sector, however has been extended in other sectors. The current study analyzes the implantation process standard in the subcontractors of the one clothing industry located in the south of Santa Catarina. The accreditation goods occurs generally certification, being sine qua non condition for the keeps on running. It is important to note that clothing industry is composed of the steps: spinning, weaving, and benefit process, being the clothing industry the final step.
Keywords: outsourcing; quality; certification ABVTEX